Baseline Predictors of Singular Action Among Participants With Multiple Health Behavior Risks. Issue 5 (May 2016) - Yusufov, Miryam; Prochaska, James O.; Paiva, Andrea L.; Rossi, Joseph S.; Blissmer, Bryan; Redding, Colleen A.; Velicer, Wayne F.
Purpose: Previous studies found that treatment effects can change two behaviors, but not one. This study examined baseline transtheoretical model constructs as three alternative predictors (stage of change, effort, and severity) of singular action among participants with co-occurring health behavior risks. Design: The study examined participants at risk for three pairs of behaviors (sun and smoking; smoking and diet; and diet and sun). Analyses were conducted with participants who changed only one behavior in a pair (singular action). Setting: School and home-based behavior change programs recruited participants via schools, worksites, and physician practices. School, worksite, medical, and home-based prevention programs were the study setting. Subjects: The sample (N = 3213) was age 44.6 years (SD, 11.1 years), 94.6% white, and 63.7% female. Measures: Stages of change, effort, and severity variables were measured. Analysis: Pooled data were analyzed using logistic regressions from three randomized controlled trials. Results: Across all three behaviors, stage of change, effort, and severity effects were consistently related to behavior change at 24 months. Change efforts on one behavior were related to change on another behavior. Baseline sun severity (odds ratio, .97 [.94, 1.00]; p = .046) and smoking severity (odds ratio, .89 [.80, .98]; p = .019) were significant predictors of change on diet at final follow-up. Conclusion: Stage of change was the biggest predictor. Problem severity was the smallest predictor of change at 2-year follow-up. Four of six predictors were within behaviors, whereas two were between.